The Moral Dilemma to Antibiotic Overprescription - Brull, Kate (Kansas State University. Dept. of Philosophy, 2019)
When creating our final project for Moral Philosophy we were tasked with investigating a moral issue. My ethical concept centered around the morality of antibiotic prescription. In particular I reviewed three main moral concepts in the topic being 1. Should our current use of antibiotics be restricted our of consideration for future generations? 2. Who is the physician's main moral duty towards a) future of public health b) current patient demands 3. How much responsibility falls on the patient to refute antibiotic treatment? Within searching to answer these questions I including many philosophical concepts such as the use of a prisoner's dilemma in order to better understand the topic.
Kirmser Undergraduate Research Award - Individual Freshman category, grand prize
Keywords: Antibiotic Overprescription; Bullet Journal; BuJo; Public Health; Ethics; Moral Responsibility